Transformation of the farm segment of the aquaculture value chain in southern Bangladesh - Ali, Hazrat; Haque, Md. Mahfuzul; Khondker, Murshed-E-Jahan (Elsevier, 2025)
Aquaculture in Bangladesh has experienced rapid growth over the last three decades, yet technological changes in the farming segment remains underexplored. To address this gap, we surveyed 721 farmers across seven districts in southern Bangladesh from November 2020 to February 2021. The result showed moderate growth in aquaculture, with an 11 % increase in farmers and a 15 % rise in waterbodies over the past decade. Farmers cultivated diverse aquatic species, with carp dominating production at 56 % followed by crustaceans (16 %) and tilapia (14 %). Shrimp are more highly susceptible to disease than fish and prawn but, only 19 % of farmers adopted measures to enhance survival. The study noted a shift from shrimp to prawn and from crustaceans to fish due to disease, market demand, and environmental factors, resulting in intensification and greater use of floating feed over the last decade. A mere 0.55 % of farmers reported losses, spoilage, or wastage during harvest or between harvest and sale of aquatic products, with the volume being minimal at just 0.52 %. Aquaculture production segment generated 401,536 full-time equivalent (FTE) on-jobs in the seven surveyed districts, predominantly for family labor. This segment also demonstrates strong profitability, with an average benefit-cost ratio (BCR) of 1.98, indicating nearly a twofold return on investment. This study highlights the evolving dynamics of aquaculture in southern Bangladesh, revealing modest growth, increased species diversification, and shifts in production practices, which underscore the sector's profitability and need for improved technological adoption on a global scale.